In utero negativization of Zika virus in a foetus with serious central nervous system abnormalities. (May 2018) - Rodó, C.; Suy, A.; Sulleiro, E.; Soriano-Arandes, A.; Antón, A.; García-Ruiz, I.; Arévalo, S.; Vázquez, É.; Vázquez, A.; de Ory, F.; Sánchez-Seco, M.P.; Rodrigo, C.; et al.
Abstract: We describe a case of a pregnant woman with Zika virus (ZIKV) infection and a foetus with severe brain malformations. ZIKV tested positive in amniotic fluid at 19 weeks but was negative at delivery. The newborn did not meet the case definition of congenital ZIKV syndrome because neither ZIKV RNA nor IgM antibodies were detected; however, prenatal brain lesions were confirmed after birth (Graphical Abstract). Graphical abstract: Timeline of significant events. *Serum, urine, vaginal swab, cervicovaginal lavage and endocervical swab. CHKV, chikungunya virus; CSF, cerebrospinal fluid; C t, amplification cycle threshold; CT, computed tomography; DENV, dengue virus; MRI, magnetic resonance imaging; RT-PCR, real-time PCR; US, ultrasound; ZIKV, Zika virus.